Ripley's believe it or not! : unbelievable stories for guys - Proud, James; Tibballs, Geoff (Orlando, Fla. : Ripley Pub., 2012)
A collection of true stories and miscellaneous facts compiled specifically for men.
Transport -- Science -- Sports and Games -- Business -- Crime and Laws -- History -- Natural World -- Body -- Mysteries -- Digital/Tech -- Arts -- Politics -- Food.
Adult
Keywords: Curiosities and wonders; Curiosities and wonders